2001
DOI: 10.3758/bf03206382
|View full text |Cite
|
Sign up to set email alerts
|

Interrupting recognition memory: Tests of familiarity-based accounts of the revelation effect

Abstract: Watkins and Peynirciog Ïlu (1990) found that, in recognition memory tasks, when items are preceded by a problemsolving task, such as doing an anagram, those items are more likely to be judged as "old," regardless of whether they have been presented in the study list (targets) or not (lures). This outcome was initially labeled the revelation effect, because the problem-solving task involved the probe word that was revealed in the solution to the task prior to the recognitiontest. Westerman and Greene (1998), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 19 publications
(37 reference statements)
2
40
1
1
Order By: Relevance
“…In some circumstances, memory illusions (the false belief that something was previously encountered) seem to be the product of changes in decision criterion rather than changes in the actual quality of memory (McDermott & Watson, 2001;Niewiadomski & Hockley, 2001;Verde & Rotello, 2003;Whittlesea, 2002). According to SDT, criterion change has no effect on the characteristics of the evidence distributions, whereas a change in discrimination sensitivity does imply a change in distributional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…In some circumstances, memory illusions (the false belief that something was previously encountered) seem to be the product of changes in decision criterion rather than changes in the actual quality of memory (McDermott & Watson, 2001;Niewiadomski & Hockley, 2001;Verde & Rotello, 2003;Whittlesea, 2002). According to SDT, criterion change has no effect on the characteristics of the evidence distributions, whereas a change in discrimination sensitivity does imply a change in distributional characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A possibility offered by Niewiadomski and Hockley (2001) is that the revelation task causes one to temporarily lose track of the appropriate criterion setting. Another, offered by Hicks and Marsh (1998), is based on Hirshman's (1995) observation that response bias becomes more liberal as the difficulty of the recognition test increases.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one might expect that a revelation task requiring more cognitive resources would exacerbate the interaction between revelation and memory tasks. However, Niewiadomski and Hockley (2001) showed that the size of the revelation effect does not change when recognition is preceded by two revealed items rather than one. Using anagrams as revealed items, Peynircioglu and Tekcan (1993) found an analogous result: There is no correlation between revelation effect size and anagram completion time.…”
Section: Underlying Mechanismsmentioning
confidence: 95%
“…Niewiadomski and Hockley (2001) suggested that disruption from the revelation task causes the subject to temporarily forget the criterion setting called for by the experimental context. Why this would consistently lead to more liberal responding is unclear.…”
Section: Familiarity Change or Response Bias?mentioning
confidence: 99%